Norrie Disease Gene Mutation in a Large Costa Rican Kindred With a Novel Phenotype Including Venous Insufficiency - Rehm, Heidi L. (1997)
Artículo científico -- Universidad de Costa Rica, Instituto de Investigaciones en Salud. 1997